Self-efficacy in life skills, career adaptability and school competences: an exploratory study - Sagone, Elisabetta; Nucifora, Marcella; Frischetto, Simona Maria; Imbrogliera, Chiara; Indiana, Maria Luisa; De Francisci, Gaetana; Brundo, Maria Violetta (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Exploring self-efficacy in life skills, career adaptability, and high school skills that help students make responsible choices for their future was the main purpose of this study. Sample: 6.250 students attending Secondary Schools in Eastern Sicily. Measures: the Career Adaptability Inventory, the Perceived Self-efficacy Scale in Life Skills, the High School Competencies Scale. Results: high sense of self-efficacy in life skills corresponds to a greater ability to anticipate changes and imagine the future in changing contexts, also in the light of non-cognitive school skills that predict success and support psychological growth, integrity, and well-being.